2021
DOI: 10.1111/dme.14512
|View full text |Cite
|
Sign up to set email alerts
|

For a high fat, high protein breakfast, preprandial administration of 125% of the insulin dose improves postprandial glycaemic excursions in people with type 1 diabetes using multiple daily injections: A cross‐over trial

Abstract: Controlling postprandial glucose variability remains a challenge for people living with type 1 diabetes. In addition to carbohydrate, recent systematic reviews have identified fat and protein as modifiers of the postprandial glycaemic profile. 1,2 Dietary fat and protein have been shown to significantly increase and delay the peak glucose excursion 3,4 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…15,29 The remaining three studies included participants only using multiple daily injection (MDI) therapy. 21,23,28 All studies used rapid-acting meal insulin. Twelve of the included studies reported optimising participants' insulin doses prior to starting the study.…”
Section: Insulin Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…15,29 The remaining three studies included participants only using multiple daily injection (MDI) therapy. 21,23,28 All studies used rapid-acting meal insulin. Twelve of the included studies reported optimising participants' insulin doses prior to starting the study.…”
Section: Insulin Therapymentioning
confidence: 99%
“…To measure postprandial glucose levels six studies used continuous glucose monitoring, 17,[25][26][27][28][29] three used venous blood testing, 5,15,18 six used capillary blood testing 13,14,[20][21][22][23] and a further three studies used a combination of continuous glucose monitoring and capillary blood testing. 16,19,24 Studies measured glucose for 3, 14,16…”
Section: Postprandial Glucose Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Two papers this month explore these challenges for people with type 1 diabetes and, importantly, explore potential strategies for people using a multiple dose injection regimen as well as for insulin pump users. 2,3 Perhaps unsurprisingly, high-fat, high-protein meals require additional insulin to minimise post-prandial glucose, but the finding that this can be safely achieved without an increase in exposure to early or late hypoglycaemia is particularly reassuring. These are small studies and, as always, inter-individual variability means that one solution will not be suitable for everyone living with type 1 diabetes, but simple, clear, practical guidance can be delivered based on the data, ensuring we continue to improve the effectiveness of peripherally delivered insulins.…”
mentioning
confidence: 99%